Introducing blended learning into the process of vocational training of practical instructors of the sewing profile - Bykova, T. (Problems of Engineer-Pedagogical Education, 2021)
The relevance of the article is explained by the need for modernisation of vocational training of practical instructors of the sewing profile. The importance of blended learning in the research of domestic scientists is revealed. The relationship between the features and opportunities that reveal the pedagogical potential of the studied innovation is clarified. The list of opportunities reveals the admissibility of blended learning by combining different types of learning using a wide range of pedagogical technologies, tools and methods that build models of blended learning, such as a station rotation model, a laboratory rotation model, an «inverted learning» model, an individual rotation model, a flexible model, a self-mixing model, and a virtual enriched model. Selection, combination, modification or creation of new models is carried out situationally. The outlined features of blended learning are proved to determine its uniqueness and technological effectiveness. The article substantiates that blended learning can be gradually introduced if higher learning institutions of vocational education interested in its implementation fulfil licensing conditions. A set of interrelated organisational measures – pedagogical conditions – allow educators to make managerial decisions, with the support of the administration, and to carry out vocational training of practical instructors of the sewing profile. The paper clarifies the importance of motivating students to realise the potential of using digital learning technologies in the training process and reveals the pedagogical potential of the most widespread models of blended learning in the field under investigation. Special emphasis is put on the fact that the effectiveness of vocational training is determined by the presence of a functional informational and educational environment. The implementation of these pedagogical conditions calls for the readiness of both teaching professionals and administrative staff to introduce blended learning, which necessitates having an appropriate level of digital competence and motivation to incorporate innovative pedagogical activities into the training process.